THE ROLE OF BIOTECHNOLOGY IN PROCESSING JACKFRUIT SEED WASTE TURNS INTO BIOETHANOL - Trivena myta manik; Ecclesia Siregar; Elva Damayanti Girsang; Yuli Bella Shinta Simamora; Ramlan Silaban (DIVERSITAS HAYATI, 2024)
The jackfruit plant is a type of tropical fruit plant that is multifunctional and can be planted in tropical areas at an altitude of less than 1,000 meters above sea level. Research has been carried out on making bioethanol from waste jackfruit seeds (Artocarpus heterophyllus Lamk). This research aims to find out whether jackfruit seed waste can be used as raw material for making biethanol and to determine the effect of pH on the fermentation process. This research used jackfruit seeds which were hydrolyzed with H2SO, 2.5% for 3 hours at a temperature of 70 °C, then the glucose content was measured and fermented at varying pH = 3, 4, 5, and 6 for 48 hours. The highest bioethanol content of jackfruit seeds was achieved during 4 days of fermentation with an alcohol content of 13.19%.